Social Media in the Public Sector Field Guide : Designing and Implementing Strategies and Policies - Mergel, Ines, 1972 and Greeves, Bill (San Francisco Jossey-Bass, 2013)
This hands-on practical guide (and companion to the Social Media in the Public Sector) offers a ready-to-use reference to help readers move smoothly through the development and deployment of effective new media strategies and policies within their own organizations.
Include Illustrations,Notes and Index
Keywords: Internet in public administration